A5.9 Values of B Lymphocyte Subpopulations (Healthy Population) using flow Cytometry a Starting Point for any study. (25th February 2013) - Munoz, A; Hernández, R; Uceda, J; León, M; Gallo, F; Martínez, R; Rodríguez, S; Velloso, ML; Cid, N; González, P; Mayordomo, L; Rejón, E; et al.
Abstract : Background: Flow cytometry is a widely used technique nowadays for the determination of cell subpopulations in the study of autoimmune, infectious and tumoral diseases. Our goal is to study the means and medians of B lymphocyte subpopulations in healthy population, to thereby have reference limits with which being able to compare when carrying out studies in population with autoimmune diseases. Methods: We studied 50 healthy patients. Male/female: 25/25. Age: 18–65 years. Previously, it was checked that none of these patients had any autoimmune diseases nor any other disease or condition causing lymphopenia or lymphocytosis. The fluorochromes used were: CD3, CD19, CD38, CD27 and IgD. Results: Conclusions: Knowing the mean, medians and standard deviations of the B lymphocyte subpopulations subsets is important in helping to compare these results with those obtained in studies of patients with autoimmune diseases. In most cases, conclusions drawn after the study with flow cytometry are based on knowing how these subpopulations vary with respect to healthy people in order to draw conclusions about what subpopulations are involved the most in the pathogenesis of the disease. We believe, therefore, important to deepen in studies of this kind in order to clarify more situations of normality in the world of flow cytometry: a technique that is increasingly taking more importance in the understanding of autoimmune diseases.